Pengaruh Budaya Organisasi terhadap Kualitas Pelayanan Pegawai di Kantor Desa Puncak Harapan Kecamatan Maiwa Kabupaten Enrekang - Herwinda Herwinda; Kamaruddin Sellang; Hardianti Hardianti; Barisan Barisan (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
Organizational culture is a system of values and norms that apply in the work environment and influence how employees provide services to the community. This study aims to determine the extent of the influence of organizational culture on the service quality of employees at the Puncak Harapan Village Office, Maiwa Sub-district, Enrekang Regency, as well as to identify the factors that influence this organizational culture.This research uses a descriptive quantitative method, with data collection techniques through observation, questionnaires, and literature studies. The sample in this study consisted of 81 community members out of a total population of 487 people who had received services from the village office staff. The data obtained were analyzed using validity tests, reliability tests, and simple linear regression with the help of IBM SPSS version 26. The results of this study indicate that organizational culture has a significant influence on the service quality of employees at the Puncak Harapan Village Office, Maiwa Sub-district, Enrekang Regency. Based on the recap of the organizational culture variable, the percentage result of 70% falls into the “good” category, and the service quality variable also falls into the “good” category with a percentage of 68%. Meanwhile, the factors influencing organizational culture towards service quality resulted in 64%, which is also in the “good” category